New Insights into HIV/AIDS-Associated Cryptococcosis. (25th February 2013) - Antinori, Spinello
Abstract : Cryptococcal meningitis is a life-threatening opportunistic fungal infection in both HIV-infected and HIV-uninfected patients. According to the most recent taxonomy, the responsible fungus is classified into a complex that contains two species ( Cryptococcus neoformans and C. gattii ), with eight major molecular types. HIV infection is recognized worldwide as the main underlying disease responsible for the development of cryptococcal meningitis (accounting for 80–90% of cases). In several areas of sub-Saharan Africa with the highest HIV prevalence despite the recent expansion of antiretroviral (ARV) therapy programme, cryptococcal meningitis is the leading cause of community-acquired meningitis with a high mortality burden. Although cryptococcal meningitis should be considered a neglected disease, a large body of knowledge has been developed by several studies performed in recent years. This paper will focus especially on new clinical aspects such as immune reconstitution inflammatory syndrome, advances on management, and strategies for the prevention of clinical disease.